Ankle Brachial Index and Subsequent Cardiovascular Disease Risk in Patients With Chronic Kidney Disease. Issue 6 (June 2016) - Chen, Jing; Mohler, Emile R.; Garimella, Pranav S.; Hamm, L. Lee; Xie, Dawei; Kimmel, Stephen; Townsend, Raymond R.; Budoff, Matthew; Pan, Qiang; Nessel, Lisa; Steigerwalt, Susan; Wright, Jackson T.; et al.
Abstract : Background: The clinical implications of ankle‐brachial index (ABI) cutpoints are not well defined in patients with chronic kidney disease (CKD) despite increased prevalence of high ABI attributed to arterial stiffness. We examined the relationship of ABI with cardiovascular disease (CVD) and all‐cause mortality among CKD patients. Methods and Results: Three thousand six hundred twenty‐seven participants without clinical peripheral artery disease (PAD) at baseline from the Chronic Renal Insufficiency Cohort Study were included. ABI was obtained per standard protocol and CVD events were confirmed by medical record adjudication. A U‐shaped association of ABI with PAD, myocardial infarction (MI), composite CVD, and all‐cause mortality was observed. Individuals with an ABI between 1.0 and <1.4 had the lowest risk of outcomes. Compared to participants with an ABI between 1.0 and <1.4, multiple‐adjusted hazard ratios (95% confidence intervals) for those with an ABI of <0.9, 0.9 to <1.0, and ≥1.4 were 5.78 (3.57, 9.35), 2.76 (1.56, 4.88), and 4.85 (2.05, 11.50) for PAD; 1.67 (1.23, 2.29), 1.85 (1.33, 2.57), and 2.08 (1.10, 3.93) for MI; 1.51 (1.27, 1.79), 1.39 (1.15, 1.68), and 1.23 (0.82, 1.84) for composite CVD; and 1.55 (1.28, 1.89), 1.36 (1.10, 1.69), and 1.00 (0.62, 1.62) for all‐cause mortality, respectively. Conclusions: This study indicates that ABI <1.0 was related to risk of PAD, MI, composite CVD, and all‐cause mortality whereas ABI ≥1.4 was related to clinical PAD. These findings suggest that ABI cutpoints of <1.0 or ≥1.4 for diagnosing PAD and ABI <1.0 for CVD risk stratification should be further evaluated among CKD patients.